123k views
4 votes
Can you walk me through the steps​

Can you walk me through the steps​-example-1
User Aleksk
by
5.1k points

2 Answers

2 votes

Answer:

3x +4= 5x-2

3(3) +4 = 5(3) -2 (plug in the x values)

9+4= 15-2 (do the multiplication on both sides)

13= 13 (do the addition/ subtraction. pretty much all you're doing, is making sure that with the given x-value, the equation is true. and it is :))

User Oleh Demkiv
by
5.0k points
5 votes

Answer:

x = 3 is the solution

Explanation:

3x + 4 = 5x - 2

when x = 3

so plug 3 into the equation where x is

so the equation becomes:

3(3) + 4 = 5(3) - 2

Then do the multiplication on both sides

9 + 4 = 15 - 2

Then do the addition and subtracition on both sides

13 = 13

User Aayoubi
by
4.8k points